New departmental records of digitonthophagus gazella (coleoptera: scarabaeidae) in colombia (2012)
The introduced dung beetle Digitonthophagus gazella was reported for the Caribbean Region of Colombia in the 90’s. During a survey carried out along the Magdalena River new records of the presence of this species were found in the departments of Boyacá, Caldas, Cundinamarca, Santander and Tolima for the first time.